READY: relative efficacy of loop diuretics in patients with chronic systolic heart failure : a systematic review and network meta-analysis of randomised trials - Täger, Tobias; Fröhlich, Hanna; Seiz, Mirjam; Katus, Hugo; Frankenstein, Lutz (Heart failure reviews, 2019)
The majority of patients with chronic heart failure (HF) receive long-term treatment with loop diuretics. The comparative effectiveness of different loop diuretics is unknown. We searched PubMed, clinicaltrials.gov, the Cochrane Central Register of Controlled Trials and the European Union Clinical Trials Register for randomised clinical trials exploring the efficacy of the loop diuretics azosemide, bumetanide, furosemide or torasemide in patients with HF. Comparators included placebo, standard medical care or any other active treatment. The primary endpoint was all-cause mortality. Secondary endpoints included cardiovascular mortality, HF-related hospitalisation and any combined endpoint thereof. Hypokalaemia and acute renal failure were defined as additional safety endpoints. Evidence was synthesised using network meta-analysis (NMA). Thirty-four trials reporting on 2647 patients were included. The overall quality of evidence was rated as moderate. NMA demonstrated no significant differences between loop diuretics with respect to all-cause mortality, cardiovascular mortality or hypokalaemia. In contrast, torasemide ranked best in terms of HF hospitalisation, and there was a trend towards benefits with torasemide with regard to occurrence of acute renal failure. Sensitivity analyses excluding trials with a follow-up < 6 months, trials with a cross-over design and those including < 25 patients confirmed the main results. We found no significant superiority of either loop diuretic with respect to mortality and safety endpoints. However, clinicians may prefer torasemide, as it was associated with fewer HF-related hospitalisations.